2003
DOI: 10.4267/2042/23920
|View full text |Cite
|
Sign up to set email alerts
|

Le concept de masse en physique : quelques pistes à propos des conceptions et des obstacles / The concept of mass in physics : some elements about conceptions and obstacles

Abstract: 41 Damien GIVRY AbstractThis study deals with students'diffictulties during the learning of the concept of mass in school. In order to better understand these difficulties, we have studied the history of this concept and analysed curiccula. After this work, we have elaborated a questionnaire, that we proposed to students from the juniorhigh school to the universityand to high school teachers. Questionnaire analysis shows conceptions and obstacles concerning the concept of mass during the different stages of te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
1
2
0
1
Order By: Relevance
“…A few students even made an analogy (free falling feather and elephant) to support their ideas. That is complementary to the findings concerning gravitation in space (Gilbert et al 1982, Galili 2001, Sharma et al 2004, Brown and Clement 1992, Givry 2003, Gönen 2008) and the path of objects in outer space (Hestenes et al 1992).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…A few students even made an analogy (free falling feather and elephant) to support their ideas. That is complementary to the findings concerning gravitation in space (Gilbert et al 1982, Galili 2001, Sharma et al 2004, Brown and Clement 1992, Givry 2003, Gönen 2008) and the path of objects in outer space (Hestenes et al 1992).…”
Section: Discussionsupporting
confidence: 59%
“…However, research in physics education has shown that the use of this simple equation is not as simple as thought (Coelho 2010). Students' difficulties with the concepts in this law, including (1) the concept of force (Clement 1982, Gunstone 1987, Hallouna and Hestenes 1985, Viennot 1985, ( 2) mass (Bovet and Halbwachs 1980, Brown and Clement 1992, Galili 1993, 1995, 2001, Givry 2003, Gönen 2008, Halbwachs 1979, Halbwachs et al 1983, Heurtaux 1978, Mullet and Gervais 1990) and (3) acceleration (Coelho 2010, Tas ¸ar 2010, Trowbridge and McDermott 1981, have been investigated. These studies concern motion on Earth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…D'autres études didactiques ont déjà confirmé et soutenu que le contexte de vie quotidienne de l'élève exerce une influence sur ses réponses (Viennot, 1977(Viennot, et 1989Halloun & Hestenes, 1985 ;Finegold & Gorsky, 1991 ;Thijs & Van Den Berg, 1995 ;Palmer, 1997Palmer, et 2001Tao & Gunstone, 1999 ;Kraus & Minstrell, 2002). Certaines études didactiques ont fait également constater la résistance des conceptions dans les réponses données par des élèves à la suite d'un apprentissage (Tsai & Chou, 2002 ;Givry, 2003 ;Treagust & Duit, 2008, Potvin, Mercier, Charland & Riopel, 2011.…”
Section: Problème De Rechercheunclassified